The Influence of Birth Ball on the Longer Time I Active Phase in Babring - Popy Apriyanti; Apriyanti Aini; Rinda Lamdayani; Titin Apriyani (Indonesian Journal of Global Health Research, 2024)
Giving birth is A situation in which the baby, placenta and fetal membranes are born from the womb into the outside world. Prolonged labor is a cause of obstetric complications, leading to maternal and fetal mortality and morbidity. Active phase I still has a large number of long-term events. This study aims to see if the birthing ball has an effect on the active phase 1 process for pregnant women. This study used a quasi-experimental research method. All pregnant women in their third trimester participated in this study. The sample of this study was 30 respondents using purposive sampling technique. Data analysis was univariate, bivariate. The results of the study showed that the birthing ball intervention had an effect on the duration of the first active phase of laboring mothers. The p-value was 0.0016. If the significance value is less than the Α value (0.000 and less than 0.05). The conclusion of this study is that H0 is rejected, which means that there is a significant difference in the duration of the first active phase between the intervention group and the control group.